Coastal Urban Community Knowledge of Coastal Hazard and Conservation in Semarang towards Sustainable Development Region - Hasti Widyasamratri; Mila Karmilah (The Indonesian Journal of Planning and Development, 2019)
Coastal is the most vulnerable area in climate change, with no exception in Coastal Java island. Reveal, 65% of the Java island population is to be vulnerable to coastal hazards such as tidal flood. The northern Java coastal area has a significant position in logistic connectivity throughout areas in the entire Java island. Abrasion and sedimentation are the most frequent effect were impacted to the coastal land cover (i.e. ponds, mangrove forest, and settlement). However, there is a lack of awareness among local communities, although they directly impact of those hazards. This study aims to identify local community knowledge of coastal disaster mitigation in Mangunharjo, Tugu sub-district Semarang, by using quantitative methods. Field observation and a simple descriptive statistic were used to analyze. The result showed that the majority of the respondents has high vulnerability on coastal hazard and disaster since they are living very close to the coastal water body.